Central Bank Legal Frameworks in the Aftermath of the Global Financial Crisis - Khan, Ashraf (IMF Working Papers; Working Paper, 2017)
Drawing on the 2016 update of the IMF's Central Bank Legislation Database, this paper examines differences in central bank legal frameworks before and after the Global Financial Crisis. Examples from select countries show that many central bank laws have undergone changes in objectives, decision-making, accountability, and data collection. A wider cross-country survey illustrates the common occurrence of price stability in central bank objectives, and varying practices in defining financial stability, 'independence' versus 'autonomy,' and who within a central bank determines monetary policy. The highlighted facts illustrate the uses of the database and could be a starting point for further analyses.